Pengaruh Produk, Harga, Kualitas Pelayanan, dan Kelompok Acuan Terhadap Keputusan Pembelian Produk Ayam Geprek (Studi Kasus di Ali Fried Chicken Cabang Damarsi Sidoarjo) - Intan Putri Ekawati; Sekar Ayu Wulandari; Septine Brillyantina; Dini Nafisatul Mutmainah (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2026)
This study aims to analyze the influence of product, price, service quality, and reference groups on purchasing decisions for ayam geprek products at Ali Fried Chicken Damarsi Sidoarjo Branch, both simultaneously and partially, and to identify the dominant variable. This research employed a quantitative approach using a survey method. The sample consisted of 50 consumers selected through accidental sampling, while data were collected using a Likert-scale questionnaire. The data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics version 31.0. The findings indicate that simultaneously product, price, service quality, and reference groups have a significant effect on purchasing decisions, as shown by an F-value of 61.919 with a significance level of < 0.001. The Adjusted R Square value of 0.833 indicates that 83.3% of the variation in purchasing decisions can be explained by the variables included in the model, while the remaining 16.7% is influenced by other factors outside this study. Partially, only service quality has a significant effect on purchasing decisions, whereas product, price, and reference groups do not have a significant effect. The most dominant variable influencing purchasing decisions is service quality, as indicated by the Standardized Coefficients Beta value of 0.395. Therefore, improving service quality should be prioritized in efforts to enhance consumer purchasing decisions